Current trends in the production of lactose-free dairy products - Pavliuk, Iryna; Bandura (Kuzmyk), Uliana; Osmak (Fedchenko), Tetiana; Mykhalevych, Artur (My University, 2023)
Recently research, aimed at developing methods and technologies for more efficient use of raw materials in the food industry (including the dairy industry), is intensively conducted.
Keywords: Lactose-free dairy products; Soy milk; кафедра технології молока і молочних продуктів; кафедра фізичного виховання